RELATIONSHIP’S SATISFACTION CONNECTION WITH THE MOTIVATION OF FORGIVENESS - Dudkina, Aija; Krasta, Elza; Porozovs, Juris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of the study was to investigate whether there is a relationship betweenthe motivation of forgiveness and satisfaction with the partnership in spouses. The study was attended by 300 married respondents: 180 women and 120 men (M = 39.29, SD = 10.7). Groups were matched according to the following criteria: age (19-60 years); married. To measure motivation of forgiveness, an interpersonal motivation survey related to abuse was used: the version of 18 statements (Transgression-Related Interpersonal Motivations Inventory; TRIM-18; McCullough et al. 1998; McCullough; Root & Cohen; 2006; adaptation in Latvian by S. Brudere -Ruska and V. Perepjolkina, 2012) and couples’ satisfaction index (CSI) Funk, JL & Rogge, RD (2007) was used to measure couples’ satisfaction. The study raised the question of whether there is a relationship between the motivation for forgiveness and the satisfaction of the spouses with the relationship? There were statistically significant positive correlations between forgiveness and satisfaction, which indicates that increasing rates of forgiveness increase satisfaction rates, and a negative close correlation was obtained by avoiding and retaliation for forgiveness, indicating that, as these scales increase, they will decrease satisfaction. Most respondents of the study against their partner, who is the abuser, are showing signs of grace that can be seen in the results of this research. The results of the study are in line with previous similar studies and confirm that forgiveness contributes to the well-being of the relationship.